An analysis of the Dark Web challenges to digital policing - Montasari, Reza (Cybersecurity in the age of smart societies, 2023)
The Dark Web is the hidden group of Internet sites that can only be accessed through specific software. The Dark Web enables private computer networks to communicate anonymously without revealing identifying information. Keeping Internet activity anonymous and private can be beneficial for both legal and illegal applications. Although it is used to evade government censorship, it is also deployed for highly illegal activity. The aim of this paper is to provide a critical analysis of the technical, legal, and ethical challenges to policing the Dark Web. The most significant recommendation identified in this paper is the need for stronger national cyber security strategies, increased awareness and use of the UN Cybercrime Repository, and greater support from intergovernmental organisations. This would help to contribute towards addressing many of the technical, legal and ethical challenges concerning the multi-jurisdictional nature of Dark Web investigations and lack of reliable data and resources while ensuring transparency and accountability. The recommendations proposed in this paper are restricted by certain limitations, therefore, further research is recommended into the field of digital policing and the Dark Web.